2018
DOI: 10.1016/j.trecan.2018.03.004
|View full text |Cite
|
Sign up to set email alerts
|

Cancer as a Matter of Fat: The Crosstalk between Adipose Tissue and Tumors

Abstract: Obesity has been linked to the increased risk and aggressiveness of many types of carcinoma. A state of chronic inflammation in adipose tissue (AT), resulting in genotoxic stress, may contribute to carcinogenesis and cancer initiation. Evidence that AT plays a role in cancer aggressiveness is solid and mounting. During cancer progression, tumor cells engage in a metabolic symbiosis with adjacent AT. Mature adipocytes provide adipokines and lipids to cancer cells, while stromal and immune cells from AT infiltra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
285
0
9

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 327 publications
(297 citation statements)
references
References 106 publications
(156 reference statements)
3
285
0
9
Order By: Relevance
“…The medical records of patients who were histopathologically diagnosed with HNSCC in our medical center from April 2012 to December 2016 were retrospectively reviewed. Of those patients, a total of 152 patients were finally enrolled in the analysis according to the following inclusion criteria: (1) those who had undergone FDG PET/CT for initial staging workup, (2) who had no evidence of distant metastasis on staging workup, and (3) who had received curative or palliative treatment after staging examinations. Patients were excluded according to the following exclusion criteria: (1) those who had received any type of treatment prior to the PET/CT scan, (2) who had received only supportive care with no palliative treatment, (3) who had distant organ metastasis on staging imaging studies, (4) who had a previous history of another malignancy or major abdominal surgery, and (5) who had CT images that were in appropriate for measuring adipose tissue parameters.…”
Section: Patientsmentioning
confidence: 99%
See 1 more Smart Citation
“…The medical records of patients who were histopathologically diagnosed with HNSCC in our medical center from April 2012 to December 2016 were retrospectively reviewed. Of those patients, a total of 152 patients were finally enrolled in the analysis according to the following inclusion criteria: (1) those who had undergone FDG PET/CT for initial staging workup, (2) who had no evidence of distant metastasis on staging workup, and (3) who had received curative or palliative treatment after staging examinations. Patients were excluded according to the following exclusion criteria: (1) those who had received any type of treatment prior to the PET/CT scan, (2) who had received only supportive care with no palliative treatment, (3) who had distant organ metastasis on staging imaging studies, (4) who had a previous history of another malignancy or major abdominal surgery, and (5) who had CT images that were in appropriate for measuring adipose tissue parameters.…”
Section: Patientsmentioning
confidence: 99%
“…Recently, evidence demonstrated that adipose tissue can play a role as an endocrine organ, beyond merely as a simple storage organ of excessive energy, and can contribute to carcinogenesis and cancer progression . Body mass index (BMI), which can be simply calculated from weight and height, has been widely used to estimate the amount of adipose tissue and many previous studies demonstrated worse prognosis for patients with high BMI in various kinds of malignancies, including colorectal cancer, breast cancer, pancreatic cancer, and hepatocellular carcinoma .…”
Section: Introductionmentioning
confidence: 99%
“…Mature adipocytes provide adipokines and lipids to cancer cells, while stromal and immune cells from adipose tissue infiltrate carcinomas and locally secrete paracrine factors within the tumor microenvironment. 6 Further research and longitudinal studies are warranted to define the specific independent and additive roles of adipokines in cancer progression and reoccurrence.…”
Section: Introductionmentioning
confidence: 99%
“…An important factor associated with obesity‐induced metabolic dysregulation is alterations in the adipose tissue . Adipose tissue is a dynamic endocrine organ, which apart from serving as an energy reservoir, has biochemical and metabolic functions that are implicated in cancer incidence and progression . Many groups have found that p53 levels are elevated in adipose tissue under conditions of chronic nutrient abundance.…”
Section: Introductionmentioning
confidence: 99%